2020
DOI: 10.1021/acs.jpcc.0c05916
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Product Selectivity of Stepped Pt Surfaces for Methane Dehydrogenation

Abstract: Through density functional theory (DFT) calculations, we show that, in contrast to terrace sites of Pt(211) and Pt(111), on steplike sites of Pt(211) and Pt(110)-(2 × 1), methylene is more stable than methyl. The resulting site-dependent product selectivity for methane dissociation allows us to conciliate between theory and recent reflection absorption infrared spectroscopy (RAIRS) experiments, which might open a door to new applications of vicinal surfaces of Pt in heterogeneous catalysis and as templates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…CH 3 binds less strongly to the top site of Ni( 111) with E ad of −1.57 eV and becomes metastable on the fcc site of Pt(111) with an approximate E ad of ∼−1.33 eV (we can only find this geometry with a loose convergence criterion). The calculated adsorption energies and harmonic frequencies agree well with previous theoretical predictions, 14,16,18,26 although the predicted frequencies are systematically higher than the experimental ones, 14,22,33 due presumably to the intrinsic error in DFT as well as the harmonic approximation used in the theoretical calculations. Note that Gutieŕrez-Gonzaĺez et al 14 have applied vdW-corrected functionals to study CH 3 adsorbed on Pt surfaces and found similar site preference and site-specific vibrational frequencies as using PBE.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…CH 3 binds less strongly to the top site of Ni( 111) with E ad of −1.57 eV and becomes metastable on the fcc site of Pt(111) with an approximate E ad of ∼−1.33 eV (we can only find this geometry with a loose convergence criterion). The calculated adsorption energies and harmonic frequencies agree well with previous theoretical predictions, 14,16,18,26 although the predicted frequencies are systematically higher than the experimental ones, 14,22,33 due presumably to the intrinsic error in DFT as well as the harmonic approximation used in the theoretical calculations. Note that Gutieŕrez-Gonzaĺez et al 14 have applied vdW-corrected functionals to study CH 3 adsorbed on Pt surfaces and found similar site preference and site-specific vibrational frequencies as using PBE.…”
supporting
confidence: 83%
“…The technique can also be used to distinguish different isotopologues of an adsorbate as well as adsorption on different surface sites based on the small vibrational frequency shifts in the vibrational mode of the methyl adsorbate, offering insights into the site specificity and bond selectivity of the dissociation process. , Apart from methane dissociative chemisorption, the methyl adsorbate is also an important intermediate in many industrial processes, so a detailed understanding of the RAIRS spectra of methyl species adsorbed on different sites on metal surfaces is highly desirable. Despite some theoretical calculations based on density functional theory (DFT), ,, there remain unexplained issues in the RAIRS spectra of CH 3 adsorbate on metal surfaces.…”
mentioning
confidence: 99%
“…Experiments have even determined sticking probabilities for dissociative chemisorption at specific surface sites, making distinctions between terrace and step sites, 162,242,243 or terrace and kink sites, 243 sometimes with support from theory helping to identify the reacted species. 244 Of these experiments the most recent ones also employed initial quantum state selection. 162,243 Older MB experiments exist on e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because the nonoxidative conversion of methane is usually conducted at temperatures higher than 1000 K at which the deactivation of catalysts due to coking is a serious challenge, the coke-resistance ability of the catalysts is an important aspect deserving to be concerned. Based on previous studies, the coke deposition behavior can be evaluated by the deep dehydrogenation process of the methyl group; , i.e., the easier methyl dehydrogenates to C* or CH* species which can be strongly bonded on the surface, the easier the coking of the catalysts will be. As shown in Figure , the dissociation of CH 3 * to CH 2 * readily occurs by overcoming a barrier of 1.11 eV with an endothermic reaction energy of 0.66 eV.…”
Section: Resultsmentioning
confidence: 99%